BIOLOGICAL AND PSYCHOLOGICAL ASPECTS OF AGING IN YOUNG WOMEN IN THE CONDITIONS OF MILITARY AGGRESSION - Boiarska, Z.O.; Overchuk, V.A.; Kostenko, V.O.; Rukshenas, O.B. (World of Medicine and Biology, 2024)
This study examines the impact of wartime stress on the aging process in 95 young women in Ukraine, exploring the relationship between their chronological, biological, and psychological ages. Utilizing comprehensive assessment methods, including the measurement of biological age, psychological age, aging rate, anxiety levels, stress resilience, and positive mental health, the research highlights how prolonged stress accelerates biological aging. It was found that chronological age has a stronger connection with psychological age than with biological age, with significant differences in aging rate among groups. Specifically, the group with accelerated aging shows a higher biological age but a lower psychological age, which may indicate less awareness of aging or an optimistic tendency to assess one’s health. Meanwhile, high stress resilience in this group may indicate adaptation to stress at the expense of physiological resources, leading to rapid aging. The findings underline the need for developing strategies to support mental health and counteract biological aging in stressful conditions, pointing to the complexity of the interaction between stress and aging.